Virtual communication and Project Work - Compaoré, Wendpanga Nelly (Jihočeská univerzita, 2021)
The topic is remote work and focuses specifically on remote work in a multicultural team. The objective of this thesis is to analyze qualitatively through interviews of people who worked in a multicultural team before and after covid in order to measure the efficiency of their work.
Virtual communication and Project Work
Keywords: Virtual communication; communication; Project management.; Virtual communication; communication; Project management.